059 Pacemaker implantation using real-time ultrasound guidance for subclavian vein access. (16th May 2012) - Darlington, E L; Rittoo, D; Patel, B; Choi, K
Abstract : Background: Subclavian vein access using anatomical landmarks for guidance is widely used and is known to carry risks of serious complications. While the use of ultrasound imaging in cannulating the internal jugular vein is well established, there is currently no similar recommendation for subclavian vein puncture. This study evaluates the use of real-time ultrasound imaging for cannulating the subclavian vein over the first rib during pacemaker implantation. Methods: Over a 2-year period, 112 consecutive patients were studied prospectively using the ultrasound technique. They were compared with 100 consecutive patients in whom the anatomical landmark technique had been used. The same standard equipment for venous cannulation and pacemaker implantation was used by a single operator in both groups. The subclavian vein and artery were imaged in cross-section over the first rib using a portable ultrasound machine (sonosite MicroMaxx) equipped with a vascular transducer. The vein was identified by its medical location and its deformation to digital compression. Its diameter (d) and distance (s) from the skin surface were measured. The puncture technique is as shown. Results: There were no significant differences between the two groups (ultrasound vs anatomical landmark) with respect to age (77±10 vs 78±9 years, ) sex (61% vs 65% male), body mass index (26±5 vs 26±4 kg/m 2 ) or history of hypertension (46% vs 49%), ischaemic heart disease (37% vs 41%), heart failure (21% vs 26%), diabetes (15% vs 17%) or dual chamber pacemakers (59% vs 47%). Median d was 0.9 cm (range 0.4–1.5) and s 1.8 cm (range 0.9–3.2). The subclavian vein was successfully punctured with ultrasound guidance in all patients and there was no pneumothorax. In contrast subclavian vein access failed in seven patients (p=0.004) and pneumothorax occurred in four patients (p=0.03) in the anatomical landmark group. Further advantages of the ultrasound technique were speed of access, minimal discomfort to patients, smooth passage of introducer and multiple leads under the clavicle and identification of patients at risk of air embolism. There was no death, haematoma or wound infection in either group. Conclusions: Puncture of the subclavian vein using ultrasound guidance is superior to the anatomical landmark technique. It eliminates the risk of pneumothorax and failure of access. It should be used routinely in patients undergoing implantation of pacemakers and other rhythm devices.